Invasive micropapillary carcinoma of the breast had poor clinical characteristics but showed no difference in prognosis compared with invasive ductal carcinoma. Issue 1 (December 2016) - Li, Guanqiao; Yang, Shiping; Yao, Jia; Wang, Zhenping; Yao, Guangyu; Liu, Mingfeng; Ye, Changsheng
Abstract Background It is controversial for prognosis of invasive micropapillary carcinoma (IMPC) compared with invasive ductal carcinoma (IDC) of the breast. To better understand the difference between IMPC and IDC prognoses, we conducted this retrospective study. Methods Data from 33 patients with IMPC were retrospectively reviewed, and the clinicopathologic characteristics and survival status were compared with those of 347 patients with IDC who were treated during the same period. Results The IMPC cases were of larger tumor size, greater proportion of nodal involvement, and an increased incidence of lymphovascular invasion compared with IDC cases. The overall survival (OS), local relapse-free survival (LRFS), distant metastasis-free survival (DMFS), and failure-free survival (FFS) rates were not significantly different between IMPC and IDC. The 3-year OS rate was 97 vs 94.2 % for the IMPC and IDC patients, respectively. The 3-year FFS rate was 87.9 vs 86.2 % for the IMPC and IDC patients, respectively. For IMPC patients, the 3-year LRFS rate was 93.9 % and in IDC patients was 89.0 %. The 3-year DMFS rates of IMPC patients was 90.9 % and IDC patients was 89 %. Conclusions IMPC had poor clinical characteristics, but it showed no difference in OS, FFS, LRFS, and DMFS compare with IDC.